Is Brazil Found Here? The construction of possible worlds through of the Brazil brand by young Catalans - de Oliveira Sampaio, Adriano; Martins, Inés (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
This article analyzes the sense production that a group of young Catalans came up with after seeing some advertising pieces about Brazil’s self-promotion campaign (2011-2014) abroad and after some posters’ presentations about the advertising campaign “Brazil. The world is here”. Discourse Analysis and focus groups were used as a technique to analyze and to collect the interviews. The results show us that the binomial similarity / difference - essential for a brand positioning construction - is practically non-existent in those campaigns, which causes a homogenization of them in several countries.